Literature survey on enhancement of MOM for intelligent cross-platform communications in service oriented architecture - Ibrahim, N.M. (Springer Verlag, 2019)
Presently, numerous of different middleware available to connect different types of application, namely Message Oriented Middleware (MOM), Message Broker, Enterprise Service Bus (ESB) and Content-Centric Middleware. MOM is the most widely used as a tool to enable the communications between distributed applications where the execution or event notifications are delivered between applications through message. MOM provides program-to-program connection by message passing. Most of MOM environments are implemented using queued message store-and-forward capability, which is Message Queuing Middleware (MQM). In addition, an intelligent cross-platform communications can be defined as the computer system that enables self-coordination to distribute computing resources and adaptive to the new environment while hiding fundamental complexity from the users. Generally, intelligent system has the competence of self-management to overcome the rapidly growing complexity in computing application. The application makes decisions on its own by using the rules that have been identified. Intelligent system also provides an adaptive and dynamic environment for the process of communication. The framework of intelligent system, fundamentally consist of intelligent elements. Each element performs a fixed function and interacting with other elements in a very dynamic environment. Â© Springer Nature Switzerland AG 2019.